If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(m + -1) + -8(m + 5) = -49 Reorder the terms: 9(-1 + m) + -8(m + 5) = -49 (-1 * 9 + m * 9) + -8(m + 5) = -49 (-9 + 9m) + -8(m + 5) = -49 Reorder the terms: -9 + 9m + -8(5 + m) = -49 -9 + 9m + (5 * -8 + m * -8) = -49 -9 + 9m + (-40 + -8m) = -49 Reorder the terms: -9 + -40 + 9m + -8m = -49 Combine like terms: -9 + -40 = -49 -49 + 9m + -8m = -49 Combine like terms: 9m + -8m = 1m -49 + 1m = -49 Add '49' to each side of the equation. -49 + 49 + 1m = -49 + 49 Combine like terms: -49 + 49 = 0 0 + 1m = -49 + 49 1m = -49 + 49 Combine like terms: -49 + 49 = 0 1m = 0 Solving 1m = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Divide each side by '1'. m = 0 Simplifying m = 0
| 8x+12=4x-7 | | -20x-x=x-x-147 | | 7(w+4)= | | 70=2*a | | 7x-3x=16 | | 10(-8+5n-6m)= | | -2(x+6)=24 | | 7(-0.25)+12=8-9(-0.25) | | 27-2z=63-6z | | 6x-(5x-1)=2 | | 0.5+2x=3x | | 11-14=-3x | | .05x-1=-1 | | 5y+9=41 | | x-0=-5(y-1) | | .4x+.05(4-x)=.1(23) | | -4x=-7 | | 4+2m=16-6 | | 0=y+3x-3 | | 1=(1/3)a-5 | | 4(3x-9)-11x=7 | | .03x=.24 | | 10s^3=30s^2 | | 10y-y= | | -5+7x+3=33 | | v^3+5v^2=0 | | -7(10-8)-(t+4)=11 | | 4(x-3)=-5x+15 | | 8u^2+u-20=0 | | 3(4w-3)-3w=3(3w-2) | | 4+2x=-3+-6x | | 8.3+x=0.1 |